2017
DOI: 10.1016/j.jacep.2017.01.017
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the PR Interval in Patients Receiving Cardiac Resynchronization Therapy

Abstract: Baseline PR interval does not affect clinical outcomes or reverse remodeling with CRT in mild HF. (Resynchronization Reverses Remodeling in Systolic Left Ventricular Dysfunction [REVERSE]; NCT00271154).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…In contrast to the results of the MADIT-CRT subanalysis, a subanalysis of the REVERSE-trial showed no significant association of PR prolongation to benefit from CRT at all. That study, however, used a cut off for PR interval prolongation of 180 ms (median of population); possibly, this lower cut off may contribute to the absence of any effect as PR prolongation substantially less than 230 ms may not result in the proposed negative haemodynamic consequenses [9]. Also, in a retrospective CRT study involving 291 LBBB patients, it was found that patients with PR interval > 200 ms had less reduction in QRS duration and QRS area and shorter survival free of heart transplantation or LV assist device implantation [25].…”
Section: Pr Prolongation In Non-lbbbmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the results of the MADIT-CRT subanalysis, a subanalysis of the REVERSE-trial showed no significant association of PR prolongation to benefit from CRT at all. That study, however, used a cut off for PR interval prolongation of 180 ms (median of population); possibly, this lower cut off may contribute to the absence of any effect as PR prolongation substantially less than 230 ms may not result in the proposed negative haemodynamic consequenses [9]. Also, in a retrospective CRT study involving 291 LBBB patients, it was found that patients with PR interval > 200 ms had less reduction in QRS duration and QRS area and shorter survival free of heart transplantation or LV assist device implantation [25].…”
Section: Pr Prolongation In Non-lbbbmentioning
confidence: 99%
“…Subanalyses of landmark trials suggest significant differences in outcome to CRT in non-LBBB patients with a right bundle branch block (RBBB) conduction pattern, as compared with those with a non-specific interventricular conduction delay (IVCD) [1,2]. Also PR interval prolongation over 230 ms has been associated with increased benefit from CRT [8,9]. Furthermore, retrospective cohort studies have identified left ventricular activation time (LVAT), fragmented QRS (fQRS), and vectorcardiographic QRS area as alternative methods in the evaluation of electrical dyssynchrony in patients with HF and predictors of response to CRT [10][11][12][13].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…The majority of other subgroup analyses of biventricular pacing RCTs suggest greater risk when a prolonged PR interval is left untreated (control group); however, this is not universally the case (for example, the REVERSE trial). 16 Furthermore, the majority of subgroup analyses have suggested greater benefit when potentially pathological PR prolongation is shortened by biventricular pacing, but this finding is not always the case. 16 …”
Section: Pr Prolongation: a Potential Therapeutic Target In Heart Fai...mentioning
confidence: 99%
“… 16 Furthermore, the majority of subgroup analyses have suggested greater benefit when potentially pathological PR prolongation is shortened by biventricular pacing, but this finding is not always the case. 16 …”
Section: Pr Prolongation: a Potential Therapeutic Target In Heart Fai...mentioning
confidence: 99%